Penyuluhan literasi Pasar Modal bagi Masyarakat Nagari Koto Nan Duo, Kecamatan Batang Kapas, Kabupaten Pesisir Selatan - Nanda, Nanda; Reswita, Yefri; Suhanda, Mya Yuwanita; Astari, Silvy (Komunitas Manajemen Kompetitif, 2024)
Community service is organized by lecturers from the Faculty of Business and Economics, Baiturrahmah University. The purpose of this activity is to improve capital market literacy for Small and Medium Enterprises (SMEs) owners in Nagari Koto Nan Duo, Batang Kapas District, Pesisir Selatan Regency, on August 10, 2024, West Sumatra Province. Capital market literacy is part of the OJK and BEI initiatives that encourage increased understanding of the capital market among the community. We strive to support this program by delivering material on the capital market, capital market instruments, potential profits and risks. Our hope is that by delivering this material to SME owners, they will have a strong understanding of capital market literacy, be able to make wise investment decisions, and avoid fraudulent investments. The success of this activity will be seen from the participants' understanding of the concept of the capital market and their ability to make the right decisions related to investment issues. We hope that similar activities can be held in various regions so that more SME owners gain knowledge about the capital market.